The lived experience of men with advanced cancer in relation to their perceptions of masculinity: a qualitative phenomenological study. Issue 7 (16th October 2014) - Stapleton, Sarah; Pattison, Natalie
Abstract : Aims and objectives: The aim of this exploratory research was to understand how men experience their advanced cancer in relation to their perceptions of masculinity. Background: There are differences in the way men and women experience illness and health care. There are inequalities in incidence and morbidities of many diseases as well as differences in rates of help‐seeking behaviours. Theories on masculinity offer some explanation towards this. Men's experiences of advanced cancer in relation to masculinity are under reported, published literature suggests that there are certain issues or men dealing with advanced disease that justify investigation. Design: A Qualitative approach using a Husserlian Phenomenological design was conducted. Sample: Eight men (aged 26–68) all with advanced cancer, defined as advanced or metastatic disease for which the patient had exhausted all standard therapeutic options. Methods: In‐depth interviews were conducted to capture narratives of the experiences of men. Data were analysed using Colaizzi's seven stage framework. Results: Themes included thwarted ambition, changing expectations, protection and provision, stoicism and coping, images of illness versus images of masculinity, importance of being a fighter and loss. Conclusion: Findings showed that the experiences of these men were complex and should be handled sensitively. Ideas for gender‐specific interventions and further research were developed from the findings in relation to current literature. Relevance to clinical practice: A better understanding and awareness of this in this context will help nurses to consider more subtle challenges that these patients may be dealing with that in turn could affect how they cope with the burden of cancer.